Cognition and Technology in Education: Knowledge and Information - Language and Discourse - Robert de Beaugrande, (Miscelánea: A Journal of English and American Studies, 2002)
Almost from the beginnings of education, technologies in a broad sense have been present, each with its own merits and drawbacks. Computer technology has been hailed with great promise, but early results have been disappointing insofar as computer limitations have been added to human limitations. After differentiating between knowledge and information and tracing the history of technology in education as an information-catered enterprise, this paper explores the prospects for real progress from hypertechnology and describes some model projects.
Keywords: education; knowledge; information; technology; information technology; hypertechnology; hypertext; multimedia; language laboratory; programmed instruction; constructionism; intertextuality